Prolonged performance-related neuroendocrine activation and perseverative cognition in low- and high-anxious university music students. (September 2018) - Gomez, Patrick; Nielsen, Carole; Studer, Regina K.; Hildebrandt, Horst; Klumb, Petra L.; Nater, Urs M.; Wild, Pascal; Danuser, Brigitta
Highlights: We measured music students' sC, sAA and perseverative cognition (PC) for 7 days. SC and sAA output were largest on concert day; post-concert recovery was only partial. Music performance anxiety (MPA) was associated with higher concert-related PC. MPA was related to lower sC output and delayed sAA output recovery. Concert-related PC was related to day-to-day changes in sC and sAA output. Abstract: Music performances are social-evaluative situations that can elicit marked short-term neuroendocrine activation and anxious thoughts especially in musicians suffering from music performance anxiety (MPA). The temporal patterns of neuroendocrine activity and concert-related worry and rumination (perseverative cognition, PC) days before and after a concert in low- and high-anxious musicians are unknown. The first goal of the present study was to investigate the prolonged effects of a solo music performance and the effects of trait MPA on salivary cortisol (sC), alpha-amylase (sAA), and concert-related PC. The second goal was to investigate whether concert-related PC is associated with neuroendocrine activity and mediates the effects of measurement day and trait MPA on neuroendocrine responses. Seventy-two university music students collected saliva samples and reported their PC for seven consecutive days. On the fifth day, they performed solo. Measurement day and trait MPA were tested as main predictors of the diurnal area under the curve with respect to ground (sC AUCg, sAA AUCg), awakening responses, and PC. SC AUCg, sAA AUCg, and concert-related PC were highest on concert day. SC AUCg decreased only partially on post-concert days. SAA AUCg remained elevated on the first post-concert day among students with moderate to very high trait MPA. Throughout the assessment period, trait MPA was associated with smaller sC AUCg and higher concert-related PC. Concert-related PC showed significant positive associations with sC AUCg and sAA AUCg but did not mediate the effects of measurement day and trait MPA on these measures. These findings suggest that solo music performances have prolonged neuroendocrine effects and that trait MPA is an important factor having specific effects on university music students' hypothalamic-pituitary-adrenal axis, autonomic nervous system, and cognitive activity.